Militant and Nationalist Organizers: The Filipino Women in the 1906 Issues of Muling Pagsilang - Taguiwalo, Judy M. (Review of Women's Studies; Vol 8 No 2 (1998): Review of Women's Studies Volume VIII, Number 2 (July-December 1998))
---